Systematic review and overview of health economic evaluation models in obesity prevention and therapy. (2nd September 2016) - Schwander, Bjoern; Hiligsmann, Mickaël; Nuijten, Mark; Evers, Silvia
ABSTRACT: Introduction: Given the increasing clinical and economic burden of obesity, it is of major importance to identify cost-effective approaches for obesity management. Areas covered: This study aims to systematically review and compile an overview of published decision models for health economic assessments (HEA) in obesity, in order to summarize and compare their key characteristics as well as to identify, inform and guide future research. Of the 4, 293 abstracts identified, 87 papers met our inclusion criteria. A wide range of different methodological approaches have been identified. Of the 87 papers, 69 (79%) applied unique /distinctive modelling approaches. Expert commentary: This wide range of approaches suggests the need to develop recommendations /minimal requirements for model-based HEA of obesity. In order to reach this long-term goal, further research is required. Valuable future research steps would be to investigate the predictiveness, validity and quality of the identified modelling approaches.